Research on the Protection Status and Development Strategies for New Varieties of Lychee and Longan in China - Yingjie WEN; Zhixian TANG; Fachao SHI; Hailun LIU; Yonghua JIANG; Qian YAN (Guangdong nongye kexue, 2025)
【Objective】The protection of new plant varieties represents a pivotal component in fostering a synergistic industrial ecosystem that encompasses breeding, cultivation, processing, marketing, and consumption. It also serves as a fundamental driving force for promoting continuous innovation in agricultural breeding. As tropical and subtropical fruit trees originating in China, litchi and longan play a pivotal role in the development of region-specific industries and rural revitalization initiatives. A systematic analysis of application and grant patterns for plant variety rights in these fruits can offer invaluable insights for enhancing their protective framework in China.【Method】Drawing upon the variety rights announcements issued by the Development Center of Science and Technology of the Ministry of Agriculture and Rural Affairs, relevant data was systematically collected, collated, and summarized. The study concentrated on key metrics, including the annual application and authorization volumes, the duration of review and authorization processes, the primary regions of application, and the entities submitting applications for new litchi and longan varieties.【Result】As of the end of 2024, the cumulative number of new variety right applications for litchi and longan was 63 and 26, respectively, ranking 16th and 18th among fruit trees. Of these, 21 litchi and 5 longan varieties were granted protection, yielding authorization rates of 33.3% and 19.2%. The average duration for examination and authorization was 30.5 months. Applications for new variety rights of litchi and longan demonstrated pronounced regional clustering, primarily in Guangdong, Guangxi, Hainan, and Fujian provinces. Academic and research institutions emerged as the predominant applicant categories.【Conclusion】Notwithstanding the notable growth in the application volumes for new variety rights of litchi and longan in recent years, several challenges persist. These include outdated breeding techniques, a lack of diversity in breeding entity structures, inefficiencies in variety conversion, and complexities within the technical and legal dimensions of variety protection. To advance high-quality industry development, future efforts must prioritize foundational research, deepen industry-academia-research collaboration, strengthen enforcement mechanisms, and enhance public awareness to elevate new variety protection standards.